2021
DOI: 10.3390/vaccines9070690
|View full text |Cite
|
Sign up to set email alerts
|

Update on Potentially Zoonotic Viruses of European Bats

Abstract: Bats have been increasingly gaining attention as potential reservoir hosts of some of the most virulent viruses known. Numerous review articles summarize bats as potential reservoir hosts of human-pathogenic zoonotic viruses. For European bats, just one review article is available that we published in 2014. The present review provides an update on the earlier article and summarizes the most important viruses found in European bats and their possible implications for Public Health. We identify the research gaps… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 257 publications
(323 reference statements)
1
21
0
Order By: Relevance
“…Bats are considered as a major reservoir of viruses, and several studies reported the characterization of viruses closely related to human viruses confirming their potential role for zoonotic events ( Hardmeier et al, 2018 ; Yinda et al, 2018 ). Based on our study, we suggest to consider the environmental contamination by these animals as it may constitute a driver for human contamination ( Gortazar et al, 2014 ; Kohl et al, 2021 ).…”
Section: Discussionmentioning
confidence: 98%
“…Bats are considered as a major reservoir of viruses, and several studies reported the characterization of viruses closely related to human viruses confirming their potential role for zoonotic events ( Hardmeier et al, 2018 ; Yinda et al, 2018 ). Based on our study, we suggest to consider the environmental contamination by these animals as it may constitute a driver for human contamination ( Gortazar et al, 2014 ; Kohl et al, 2021 ).…”
Section: Discussionmentioning
confidence: 98%
“…Over 200 viruses have been detected in bats, some of which cause severe disease in humans and other animals 2 . For example, coronaviruses that cause severe respiratory syndromes and filoviruses that lead to fatal hemorrhagic fevers have been detected in different bat species worldwide 3 . Surprisingly, previous studies identified asymptomatic bats that harbored these pathogenic viruses 4–6 .…”
Section: Introductionmentioning
confidence: 99%
“…Bats of the genus Eptesicus are known to be hosts of several zoonotic viruses, such as rhabdoviruses that cause encephalitis and flu‐like symptoms 3 . In recent studies, Eptesicus fuscus has been reported to show a distinctive immune mechanism that involves a repressor‐binding motif in the TNF‐α promoter and suppresses inflammatory pathology 18 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations